A phase I trial of MK‐2206 in children with refractory malignancies: A Children's Oncology Group study. Issue 7 (24th March 2014) - Fouladi, Maryam; Perentesis, John P.; Phillips, Christine L.; Leary, Sarah; Reid, Joel M.; McGovern, Renee M.; Ingle, Ashish M.; Ahern, Charlotte H.; Ames, Matthew M.; Houghton, Peter; Doyle, L. Austin; Weigel, Brenda; et al.
<x xml:space="preserve">Abstract</x> Background We report results of a phase I trial designed to estimate the maximum tolerated dose (MTD), describe dose‐limiting toxicities (DLT), and characterize the pharmacokinetic profile of MK‐2206, an AKT inhibitor, in children with refractory or recurrent malignancies. Procedure MK‐2206 was administered either every other day (Schedule 1), or once a week (Schedule 2) in a 28‐day cycle. Dose escalations in increments of ∼30% were independently made in each part using the rolling‐six design. Serial pharmacokinetic (PK) studies were obtained. Biological studies include analysis of PI3K/PTEN/AKT‐cell signaling pathway in pre and post‐therapy in PBMC and in tumors at diagnosis or recurrence. Results Fifty patients (26 males, median age 12.6 years [range, 3.1–21.9]) with malignant glioma (16), ependymoma (4), hepatocellular carcinoma (3), gliomatosis cereberi (2), or other tumors (22) were enrolled; 40 were fully evaluable for toxicity (Schedule 1, n = 23; Schedule 2, n = 17). Schedule 1 DLTs included: grade 3 dehydration in 1/6 patients at 28 mg/m2; grade 4 hyperglycemia and neutropenia in 1/6 patients at 45 mg/m2; and grade 3 rash in 3/6 patients at dose level 4 (58 mg/m2). Schedule 2 DLTs included: grade 3 alkaline phosphatase in 1/6 patients at 90 mg/m2; grade 3 rash in 1/6 patients at 120 mg/m2; and grade 3 rash in 2/6 patients at 155 mg/m2. Conclusions The recommended pediatric phase 2 dose of MK‐2206 is 45 mg/m2/dose every other day or 120 mg/m2/dose weekly. PK appeared linear over the dose range studied. Pediatr Blood Cancer 2014;61:1246–1251. © 2014 Wiley Periodicals, Inc.